Financial Mismanagement: A Leading Cause of Time and Cost Overrun in Mega Construction Projects in Pakistan - Shaikh, F. A. (Engineering, Technology & Applied Science Research, 2020)
One important and well-known issue for the majority of construction projects such as buildings, roads, bridges, airports and many more projects all over the world is time and cost overrun. Project pricing and time period delay are also major issues. The current investigation is taking into consideration the mega construction projects in the provinces of Pakistan, looking into various components controlling and dominating time and cost overrun. A total of 29 factors were identified from literature work and one questionnaire was designed and distributed among 160 respondents. All collected data were analyzed by the average index method. Factors having value more than 3.6 were selected as main factors of cost and time overrun, and five factors were revealed to surpass this barrier. Time and cost overrun are of the leading financial mismanagement issues of the economy of Pakistan. This study will be helpful for stakeholders to control both cost and time overrun in the mega construction projects of Pakistan.